Genetic variation in dihydropyrimidine dehydrogenase (DPYD) gene in a healthy adult Indian population. (January 2015) - Iyer, Sandhya N.; Singhal, Rekha S.; Hegde, Madhuri R.; Ankala, Arunkanth
Abstract Background: Dihydropyrimidine dehydrogenase (DPD) encoded by DPYD gene is the major enzyme involved in metabolism of 5-flurouracil (5-FU), a pyrimidine analogue used in cancer chemotherapy. Although very effective as a cancer therapeutic drug, if not rapidly metabolized, 5-FU may prove lethal. Single nucleotide variants (SNVs) within DPYD that modulate DPD enzyme activity contribute to 5-FU toxicity. Study: This study looked for DPYD SNVs common in the Indian population that might be associated with variable DPD activity and drug toxicity. To achieve this, sequencing analysis was performed of all 23 exons and flanking intronic regions of the DPYD gene in a cohort of 50 healthy adult Indians. This study detected 22 SNVs including intronic, synonymous and non-synonymous changes in the DPYD gene, of which six have not been documented before. Allelic frequency was calculated for the observed variants and linkage disequilibrium (LD) analysis was performed on variants with frequency ≥0.1 to identify haplotypes. Conclusions: This study provides a brief overview of the genetic polymorphism in DPYD in Indians and emphasizes the need for a large scale extensive study to establish markers associated with the frequently observed variable drug metabolism.